Critical Discourse Analysis of Propaganda Created by Mirror.co.uk and Thedailystar.net for Concerning Islamophobia - Pahuse Wanda; Hamzah Hamzah; Leni Marlina (English Language and Literature, 2020)
This research investigates the propaganda techniques used by the online news author concerning Islamophobia. This study used lexical choices by Fairlough’s textual analysis and the aim of this study is to identify the words including verb, noun, adverb and the propaganda techniques that used by the news author to describe Islam and Muslims in their news articles. Types of research used in this study are descriptive qualitative research. The results of this study are from mirror.co.uk found that the author used 72 words including verb, noun, and adverb for describing Muslims. Meanwhile, thedailystar.net found that the author used 83 words with negative meaning for describing Islam. From the analysis of the lexical choice, the top frequencies used by the two media are terrorists, extremists, radicals and militants. From the analysis of propaganda techniques, found that both media used name-calling, card stacking, and testimonial propaganda techniques. The two media used name-calling techniques in total 155 words, card stacking in total 31 sentences, and 11 sentences are testimonial propaganda techniques. Both media also used the words which have negative connotation, and images. In such manner, it is proposed that the world of Islam be aware of this false opinion used negative propaganda against Islam and take fitting and convenient measures with the goal that they could present the genuine idea of this holy religion to the world and diminish the quantity of Islamophobic assaults on Muslim people group all through the world.